2000
DOI: 10.1289/ehp.00108533
|View full text |Cite
|
Sign up to set email alerts
|

Serum clara cell protein: a sensitive biomarker of increased lung epithelium permeability caused by ambient ozone.

Abstract: Ozone in ambient air may cause various effects on human health, including decreased lung function, asthma exacerbation, and even premature mortality. These effects have been evidenced using various clinical indicators that, although sensitive, do not specifically evaluate the O(3)-increased lung epithelium permeability. In the present study, we assessed the acute effects of ambient O(3) on the pulmonary epithelium by a new approach relying on the assay in serum of the lung-specific Clara cell protein (CC16 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
54
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 20 publications
6
54
2
1
Order By: Relevance
“…As CC16 is synthesised and secreted almost exclusively by the lung Clara cells, the enhanced serum concentration can only be explained by a leakage of the protein across the lung epithelial barrier [16,26]. This finding is in agreement with the enhanced serum levels of CC16 obtained from cyclists exposed to O 3 in the environment, as the main oxidant in summer photochemical smog [21,27]. Notably, no association was observed between the magnitude of the O 3 -induced lung function decrements and CC16 responses, suggesting that impaired lung function was not related to epithelial injury.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…As CC16 is synthesised and secreted almost exclusively by the lung Clara cells, the enhanced serum concentration can only be explained by a leakage of the protein across the lung epithelial barrier [16,26]. This finding is in agreement with the enhanced serum levels of CC16 obtained from cyclists exposed to O 3 in the environment, as the main oxidant in summer photochemical smog [21,27]. Notably, no association was observed between the magnitude of the O 3 -induced lung function decrements and CC16 responses, suggesting that impaired lung function was not related to epithelial injury.…”
Section: Discussionsupporting
confidence: 65%
“…Support for this notion has been demonstrated in mice where O 3 -induced increases in serum CC16 are accompanied by neutrophil influx into the airways. In this study the authors also demonstrated an increased concentration in bronchoalveolar lavage fluid albumin [27]. In the present study, as in the field study of cyclists, no measurements of airway inflammation were performed.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Levels of CCSP in serum have been shown to rise after exposure to ozone (7,9,11), smoke (5), or LPS (2). The leading hypothesis is that there is increased leakage of CCSP from the airways into the blood when the epithelial layer is damaged.…”
mentioning
confidence: 99%
“…The leading hypothesis is that there is increased leakage of CCSP from the airways into the blood when the epithelial layer is damaged. This has led many to consider serum CCSP as a new noninvasive biomarker of acute epithelial damage (7,9,10,15). To properly assess the potential clinical benefits of CCSP, it is necessary to understand the steady-state distribution of CCSP in the airway and in the various epithelial cell types.…”
mentioning
confidence: 99%